Authentication process enhancements in WiMAX networks. Issue 17 (16th August 2016) - Alezabi, Kamal Ali; Hashim, Fazirulhisyam; Hashim, Shaiful Jahari; Ali, Borhanuddin M.; Jamalipour, Abbas
Abstract: Authentication is one of the most important security processes in Worldwide Interoperability for Microwave Access (WiMAX) networks. This process allows the receiver (whether base station or subscriber station) of a packet to be confident of the identity of the sender and the integrity of the message. Most attacks will attempt to violate the authentication process. If such attacks become successful, an attacker will gain an illegitimate access to network resources, thus increasing the probability of future malicious attacks. A number of algorithms and methods have been proposed to improve the security level of authentication in WiMAX networks. However, the evaluations of these algorithms and methods have always been based on a particular aspect, such as reducing overhead, protecting unauthenticated management messages, preventing WiMAX from external attacks, and protection during the handover process. Motivated by these variations, we review the state of art of WiMAX authentication mechanisms, namely, PKMv1, PKMv2, and the recent authentication protocols. We discuss their mechanisms, strengths, weaknesses, and potential countermeasures against each other. Our discussion is based on four categories, namely, enhancements, differences, advantages, and limitations. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper presents a comprehensive survey of existing and recent literature in the domain of WiMAX security, particularly on the authentication process. We attempt to assess the ongoing work in this area and consolidate existing results. Given that this paper surveys the WiMAX authentication techniques proposed in the last 7‐years, we also describe some of the earlier works in this area. In addition, the open problems and research challenges are identified and highlighted.